Sosialisasi Pengembangan Kapasitas Manajerial Kepala Sekolah SMP Kota Makassar Melalui Sistem Informasi Sekolah - Firdaus, Firdaus; Karim, Sugeng A.; Massikki, Massikki; Bakri, Hasrul (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2025)
This community engagement activity was designed to enhance the managerial capacity of junior high school principals in Makassar City through the socialization of the School Information System (SIS). In the context of information technology development, SIS is seen as a potential tool to improve administrative efficiency and school management effectiveness. The socialization activity was carried out in the form of interactive seminars and group discussions, involving 40 junior high school principals in Makassar City. The socialization material included the basic concepts of SIS, its benefits for school management, relevant features, and SIS implementation case studies. The results of the activity showed an increase in participants' understanding of the concept and benefits of SIS, as well as an increase in interest in learning more about and considering implementing SIS in their respective schools. This activity is expected to make a positive contribution to efforts to modernize education management at the junior high school level in Makassar City, through the use of information technology to support the managerial tasks of school principals.